Anemia in type 2 diabetic patients and correlation with kidney function in a tertiary care sub-Saharan African hospital: a cross-sectional study. Issue 1 (December 2016) - Feteh, Vitalis; Choukem, Simeon-Pierre; Kengne, Andre-Pascal; Nebongo, Daniel; Ngowe-Ngowe, Marcelin
Abstract Background Anemia is common in diabetic patients and increases morbidity and mortality, but its burden has been less well characterized in sub-Saharan Africans. We determined the prevalence of anemia and investigated the related factors, with a particular focus on the role of declining renal function, in type 2 diabetic patients attending a tertiary health care institution in Cameroon. Methods Hemoglobin (Hb) levels were measured in a consecutive sample of patients with type 2 diabetes, who reported for annual review at the outpatient section of the Douala General Hospital in 2013. Patients were classified as anemic according to the World Health Organisation criteria (Hb < 12 g/dl for females and Hb < 13 g/dl for males). Estimated glomerular filtration rate (eGFR) was calculated using the abbreviated Modification of Diet in Renal Disease Study Group formula. Determinants of Hb concentration and anemia were investigated using multivariable logistic regressions. Results A total of 636 patients were examined including 263 (prevalence rate 41.4 %) who had anemia. The prevalence of anemia increased significantly with deteriorating kidney function, although up to 31.9 % of patients with normal kidney function had anemia. Compared with their non-anemic counterparts, anemic diabetic patients were older, had longer duration of diabetes, lower eGFR, higher prevalence of proteinuria and diabetic retinopathy (allp  < 0.05). In multivariable logistic regressions, eGFR (p  = 0.001) and presence of retinopathy (p  = 0.023) were the independent determinants of prevalent anemia. Conclusions The prevalence of anemia is high in type 2 diabetic patients attending referral institutions in Cameroon, including among those without chronic kidney disease. Routine screening for anemia in all diabetic patients may aid early identification and correction as appropriate.